Readout of the Ghazaliyate Shams from the Perspective "self" Archetype in Jung's Thought - behnam sadeghian (Matn/Pizhūhī-i Adabī, 2018)
In Jung's Analytical Psychology “Self” is one of the important expressions. In Jung's view, self is an archetype which can be considered as base of an individual's integration and consistency. According to Jung's theory, we all grow slowly during their life time and after experiencing a process which Jung calls it "Individuation process" we become the one who we are. Jung calls the whole personality "self". From his point of view "Self" can’t be understood completely. "Self" is symbol of integration and Christ is the archetypical exemplar of human integration because Christ is an example of the divine integration. Jung has mentioned several features for "Self". On the other hand, in Ghazaliyate Shams and overall in mystical literature we face with terms such as soul "Rouh", spirit "Jan" and heart "Del" that are consistent with the schema that Jung define. In this study in addition to explaining the "Self" archetype form Jung's perspective we have also  aimed to collate it with the features of "Soul" , "spirit" or "heart" in Ghazaliyate shams and study its features.